Can depressed patients make a decision to request voluntary assisted dying?. Issue 10 (18th October 2021) - Holmes, Alex; Lange, Peter; Stewart, Cameron; White, Ben; Willmott, Lindy; Dooley, Michael; Philip, Jennifer; La Brooy, Camille; Komesaroff, Paul
Abstract: Depressive symptoms, including those as part of a major depressive disorder, are common at the end of life. A number of psychiatrists consider that a diagnosis of major depression precludes the capacity to make a decision to request voluntary assisted dying (VAD), although this is not a unanimous view. This paper uses a case of a patient in which two different psychiatric opinions were formed regarding her capacity to make the decision to request VAD. The difference of view can be related to whether major depression was diagnosed and the association made between depression and the capacity to request VAD. The view that an absence of major depression is required in order to establish the capacity to request VAD is potentially at odds with the legal definition and not necessarily in keeping with the patient's experience at the end of life.